Cryo-Electron Microscopy Methodology: Current Aspects and Future Directions. Issue 10 (October 2019) - Danev, Radostin; Yanagisawa, Haruaki; Kikkawa, Masahide
Abstract : Cryo-electron microscopy (cryo-EM) has emerged as a powerful structure determination technique. Its most prolific branch is single particle analysis (SPA), a method being used in a growing number of laboratories worldwide to determine high-resolution protein structures. Cryo-electron tomography (cryo-ET) is another powerful approach that enables visualization of protein complexes in their native cellular environment. Despite the wide-ranging success of cryo-EM, there are many methodological aspects that could be improved. Those include sample preparation, sample screening, data acquisition, image processing, and structure validation. Future developments will increase the reliability and throughput of the technique and reduce the cost and skill level barrier for its adoption. Highlights: Cryo-EM SPA requires good samples and large image datasets to produce near-atomic 3D maps of isolated proteins. Sample preparation is the main bottleneck in both SPA and cryo-ET. The current cryo-EM grid plunging technique is primitive. There is an urgent need to develop more efficient and consistent methods. Sample screening can be optimized and automated to improve the efficiency and productivity of cryo-EM. Data acquisition speed will continue to improve with prospects for at least a twofold increase in the next few years. More comprehensive data validation criteria and performance metrics must be defined and adopted as standard by the community.